TINJAUAN YURIDIS TERHADAP PERJANJIAN PINJAMAN BERDASARKAN ASAS-ASAS DALAM HUKUM KONTRAK (Studi Kasus Putusan PN.JKT.Bar No. 451/Pdt.G/2012/ PN.Jkt.Bar ) - Galvin Julio (Fakultas Hukum Universitas Pembangunan Nasional Veteran, 2024)
This memorandum is entitled Juridical Review of Loan Agreements Based on Principles in Contract Law (Case Study of PN.Jkt.Bar Decision No. 451/Pdt.G/2012/ PN. Jkt.Bar.Written By Galvin Julio Nim 2010611225, and the Final Project Supervisor Mr. Surahmad, S.H, M.H. In the decision, the judge condemned the defendant in this case Lo Nine AM Ltd, which the judge cancelled the agreement and the rest of the loan money was returned to the defendant. The case originated from the loan agreement dated 23 April 2010 in which PT. Bangun Karya Pratama Lestari borrowed money from Lo Nine AM Ltd in the amount of U$D 4,220,000, where the money was used by PT. Build Karya Pratama Lestari to buy 6 new trucks for their company operations, along with the passage of time for 2 years PT. Bangun Karya Pratama Lestari considers Lo Nine Am Ltd to have breached the contract because Lo Nine Am Ltd did not make a Deed of Agreement. Loan in Indonesian and only used English in the deed and dated 20 April 2010 PT. Bangun Karya Pratama Lestari filed an action for rescission with the West Jakarta District Court, but upon judicial review it was found that PT. Bangun Karya Pratama Lestari was the one who entered into the contract, as the agreement was made for 2 years, PT. Bangun Karya Pratama Lestari did not fulfil its obligations by paying its principal and interest debt to Lo Nine Am Ltd. From the above problems, the author obtains a legal opinion on the existing problems that are contained in Article 1320 of the Civil Code, 1338 of the Civil Code, in this article explains that the agreement that has been agreed by both parties cannot be cancelled if in the process there is no coercion, this can be seen in Article 1233 of the Civil Code.